TIRAP in the Mechanism of Inflammation - Rajpoot, Sajjan; Wary, Kishore K.; Ibbott, Rachel; Liu, Dongfang; Saqib, Uzma; Thurston, Teresa L. M.; Baig, Mirza S. (Frontiers in Immunology, 2021)
The Toll-interleukin-1Receptor (TIR) domain-containing adaptor protein (TIRAP) represents a key signaling molecule regulating diverse immune responses. Its capacity to function as an adaptor molecule has been widely investigated in relation to Toll-like Receptor (TLR)-mediated innate immune signaling. Most recent reports have described the ability of TIRAP to act as a key mediator of inflammatory signaling by coupling MyD88 with TLRs. Indeed, the ability of TIRAP to interact with diverse and different intracellular signaling molecules means it has a central role in various immune responses. Therefore, studies that elucidate the molecular basis of the different TIRAP protein-protein interactions and how this affects the inflammatory signaling magnitude are critical. This review starts by summarizing the mechanism of TIRAP recruitment to activated receptors and thereafter discusses the downstream interactions that mediate inflammatory signaling. Overall, we analyze how different TIRAP protein-protein interactions mediate the activation of major inflammatory signaling pathways and how this relates to both acute and chronic inflammatory diseases.